The Distributed Ledger Technology for the Art Market (UNWE Yearbook, 2024)
The art market seems exclusive to a limited circle of collectors due to information imbalances regarding artworks and their value. Often, one must turn to experts and auction houses to finalize a deal. In addition to artistic advice, legal consultations are also necessary, often due to third-party claims on the ownership of the artwork or cases of fraud. This article aims to explore the potential advantages of utilizing distributed ledger technology in the art market to verify and record transactions involving whole or parts of artworks, making them traceable and perhaps more easily purchasable.